(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
In Nigeria, since the last three decades there has been a tremendous pressure on forest to provide economic resources leading to unabated deforestation and the potential negative effect of such changes on forest quality, quantity and production are wide. The objective of this study was to evaluate the effectiveness of Remote Sensing and Geographic Information System (GIS) Techniques in Forest Reserve Monitoring and Prediction using Girei forest reserve of Adamawa State, Nigeria as a case study. The images of Landsat TM 1987, ETM+ 2000, Nigeriasat-1 2010 and Spot5 2015 were analyzed to derived information on environmental changes between 1987 and 2015. The results revealed that fuel wood extraction and over cultivation are the main causes of deforestation in the area. It also revealed that forest area has reduced from 177.03 km2 in 1987 to 75.98 km2 in 2015. This implies that land-use such as build up areas and cultivated areas were increasing through the time i.e. from 3.33 km2 in 1987 to 8.95 km2 in 2015. This indicated that the rate of deforestation in the area is high at about 33.68 km2 per year thereby confirming the perception of 58% of the respondent. Decrease in vegetal resource, decrease in rainfall and increase in temperature were observed as the most serious effect of deforestation in the area. The study recommends that government and traditional authorities should provide affordable alternative sources of energy to reduce pressure on fuel wood and the need to enforce environmental laws